2021
DOI: 10.1177/23780231211020236
|View full text |Cite
|
Sign up to set email alerts
|

Social Science–Based Pathways to Reduce Social Inequality in Youth Outcomes and Opportunities at Scale

Abstract: Despite a recent call for an expanded research agenda that is more likely to produce tangible societal reductions in inequality, efforts to articulate how social scientists can actually pursue this agenda remain few and far between. The central question this article addresses is, What can social scientists do to deliver the forms of knowledge that may lead to a reduction of social inequalities in youth outcomes and opportunities at large scale? Drawing on conceptualizations of inequality that pay attention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 70 publications
0
39
0
Order By: Relevance
“…In a recent special issue of Socius , Gamoran (2021), Nalani et al. (2021), and DiPrete and Fox‐Williams (2021) offered critiques on the field of sociology's response to inequality in the US, observing relative excellence in understanding inequality coupled with relative mediocrity in reducing inequality. Importantly, this collection was not wrought with impossibility and condemnation; rather, these scholars see potential in how social scientists can act as change‐agents through their science.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent special issue of Socius , Gamoran (2021), Nalani et al. (2021), and DiPrete and Fox‐Williams (2021) offered critiques on the field of sociology's response to inequality in the US, observing relative excellence in understanding inequality coupled with relative mediocrity in reducing inequality. Importantly, this collection was not wrought with impossibility and condemnation; rather, these scholars see potential in how social scientists can act as change‐agents through their science.…”
Section: Discussionmentioning
confidence: 99%
“…Using state-level data on individual children, the study identified several differences in the distribution of outcomes in EI/ECSE by child background. Findings can be used in tandem with stakeholder-engaged research to understand inequities and to develop targeted implications for research, policy, and practices that improve equity across steps in the EI/ECSE pipeline (Nalani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…First, analyses of these data only provide information on outcome distribution by child ethnicity and language, which are only proxy variables for underlying constructs such as cultural views on disability, acculturation to the US special education system, and health literacy; further research is needed to examine the interpersonal factors or relational inequities that ultimately lead to the distributional inequities identified in this study. Together, this information will provide a complete picture of interventions needed to improve equity in EI/ECSE (Nalani et al, 2021). Second, although missing data were low, data entry may have been subject to error.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Although solving this substantial problem requires a significant collaboration among experts, scholars, authorities, and people, long hours of discussions, and a considerable cost, it would have many advantages [13]. Every group of people, industry, university, and government authorities would benefit from a society without this issue [14].…”
Section: Introductionmentioning
confidence: 99%